Optimization of the Guuna Kamsel Unit and District Service in Reducing the Number of Accidents in the Kediri City Police Area - Taqi, Althaf (Advances in Police Science Research Journal, 2024)
This research is motivated by the security and safety unit of the traffic unit discussing ways to reduce the number of traffic accidents in the Kediri City Police Jurisdiction. The aim of the research is to describe the factors that influence traffic education and optimize traffic education by the Security and Safety Unit to prevent traffic accidents in the jurisdiction of the Kediri City Police. By optimizing the role and duties of traffic police, the researcher used qualitative research methods with field research, as well as theories and concepts, namely management theory and competency theory, as well as the concept of preventing traffic accidents and the concept of public education in the traffic sector. In discussing this research, researchers found that unit members had sufficient work experience, but there were still several members who had not been trained, and material was also found that had not been able to attract the public’s attention. The influencing factors are a lack of personnel, inadequate budget, and traffic education materials that are not on target to reduce traffic accidents in the jurisdiction of the Kediri City Police. Suggestions given by researchers include the need to implement education for members, hold interesting games and quizzes during the implementation of traffic education so that the delivery of traffic education can be more interesting and not boring, have a regular distribution of tasks and schedules, and use financial accommodation according to needs.